2016
DOI: 10.1093/mnras/stw1454
|View full text |Cite
|
Sign up to set email alerts
|

Stacking for machine learning redshifts applied to SDSS galaxies

Abstract: We present an analysis of a general machine learning technique called 'stacking' for the estimation of photometric redshifts. Stacking techniques can feed the photometric redshift estimate, as output by a base algorithm, back into the same algorithm as an additional input feature in a subsequent learning round. We shown how all tested base algorithms benefit from at least one additional stacking round (or layer). To demonstrate the benefit of stacking, we apply the method to both unsupervised machine learning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…The study [34], eulogize the performance of AC with mathematical ground truth in their research. In many classification experiments, the AC has been shown to outperform the other machine learning algorithms [35]- [37]. For a detailed discussion of AC, see [38]…”
Section: ) Adaboost Classifier (Ac)mentioning
confidence: 99%
“…The study [34], eulogize the performance of AC with mathematical ground truth in their research. In many classification experiments, the AC has been shown to outperform the other machine learning algorithms [35]- [37]. For a detailed discussion of AC, see [38]…”
Section: ) Adaboost Classifier (Ac)mentioning
confidence: 99%
“…18,19 Several studies have reported higher performance with Adaboost compared to XGBoost, despite the popularity of XGBoost. 20,21,22,23,24,25,26 Compared with the previous studies, this study proposes the following contributions. First, it is a novel approach to apply and compare the extensive range of data-driven machine learning algorithms for nomograms subject to SMILE.…”
Section: Discussionmentioning
confidence: 99%
“…The first two classes of methods work with a single algorithm called "weak" to generate a stronger model. While combinatorial methods combine several algorithms at once in order to have a more powerful predictive model (Nagi & Bhattacharyya, 2013) (Zitlau et al, 2016) (Alves, 2017).…”
Section: Machine Learnig Algorithmsmentioning
confidence: 99%